2006
DOI: 10.1111/j.1525-139x.2006.00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis Rounds
A Dialysis Case Presentation and Discussion
Edited by Roger A. Rodby: Severe Lactic Acidosis Treated with Prolonged Hemodialysis: Recovery After Massive Overdoses of Metformin

Abstract: We report two cases of severe lactic acidosis due to massive metformin ingestion. The first case was a 37-year-old man who was discovered several hours after ingesting 45 g of metformin. He had severe lactic acidosis (blood pH 6.81, bicarbonate 4 mEq/L, lactate 25.7 mEq/L). Despite intravenous bicarbonate therapy, he decompensated and was placed on a combination of hemodialysis and charcoal hemoperfusion for a continuous time of 25 hours. His hospital course was complicated by acute renal failure requiring a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 37 publications
1
52
0
3
Order By: Relevance
“…Seidowsky et al 6 demonstrated a bicompartmental elimination pattern of metformin by hemodialysis and found that cumulative hemodialysis duration of 15 h was associated with the return of metformin levels to the therapeutic range. The mean duration of hemodialysis in their group was 13 ± 9 h. Guo et al 15 successfully hemodialyzed two patients with severe MALA (pHs of 6.85 and 6.81) for 21 and 25 h (combined with charcoal hemoperfusion for 12 of the 25 h), respectively. Interestingly, both patients had significantly elevated lactate levels at the end of their treatments and both required further dialysis for acute renal failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seidowsky et al 6 demonstrated a bicompartmental elimination pattern of metformin by hemodialysis and found that cumulative hemodialysis duration of 15 h was associated with the return of metformin levels to the therapeutic range. The mean duration of hemodialysis in their group was 13 ± 9 h. Guo et al 15 successfully hemodialyzed two patients with severe MALA (pHs of 6.85 and 6.81) for 21 and 25 h (combined with charcoal hemoperfusion for 12 of the 25 h), respectively. Interestingly, both patients had significantly elevated lactate levels at the end of their treatments and both required further dialysis for acute renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…This two-compartment model suggests that an initial brief hemodialysis will be only partially effective in eliminating metformin. Thus it has been suggested that prolonged 15 hemodialysis is indicated in patients with severe overdose who are able to tolerate hemodialysis. Seidowsky et al 6 demonstrated a bicompartmental elimination pattern of metformin by hemodialysis and found that cumulative hemodialysis duration of 15 h was associated with the return of metformin levels to the therapeutic range.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, MALA is considered a type B lactic acidosis. However, there is a designation change to incorporate type A as well, after multi-organ dysfunction ensues and tissue hypoperfusion develops [3,16,[20][21][22].…”
Section: How Does Metformin Lead To the Development Of Lactic Acidosimentioning
confidence: 99%
“…The elimination half-life is approximately 17 h, with 90 % of the dose ingested being renally cleared within 24 h [9]. The drug has high water solubility, minimal plasma protein binding, and a large volume of distribution, being concentrated primarily in the intestinal wall, salivary glands, kidneys, and liver [1,3,10,11].…”
mentioning
confidence: 99%
“…8,11 Hemodialysis should systematically be performed in more severe forms of lactic acidosis which deteriorate despite intravenous bicarbonate therapy. 12,13 In the conclusion, metformin intoxication with suicidal intention may lead to metabolic acidosis with a high anion gap. Bicarbonate infusion in suicidal metformin overdose is able to sufficiently corTurkiye Klinikleri J Med Sci 2012;32 (2) rect the acid-base metabolism in subjects with the normal renal functions.…”
Section: Discussionmentioning
confidence: 99%